TO THE HISTORY OF THE DEPARTMENT OF PROPEDEUTICS OF INTERNAL DISEASES OF SIBERIAN STATE MEDICAL UNIVERSITY. SCIENTIFIC TRENDS, PROBLEMS AND ACHIEVEMENTS - F. F. Tetenev (Бюллетень сибирской медицины)
The history of the oldest Department of theSiberianStateMedicalUniversity– Department of Propedeutics of Internal Diseases has been presented